Survival of borderline tumors of the ovary and its prognostic factors at Dr. Cipto Mangunkusumo hospital from 1990 to 1999 (Faculty of Medicine Universitas Indonesia, 2002)
Sixty-two patients with borderline tumors of ovary were historical cohort analyzed for survival characteristics. There were 9 patients with FIGO stage IA, 9 with stage IC, 3 with stage IIIA, 2 with stage IIIB, 4 with stage IIIC, 1 with stage IV and 34 with inadequate stage tumors. Twenty one patients had surgical staging with radical surgery, 10 patient had at least a total abdominal hysterectomy and bilateral salpingo-oophorectomy, 6 patient had surgical staging with conservative surgery, 24 patient had at least a unilateral salphingo-oophorectomy or ovarian cystectomy and 1 patient had biopsy. Sixteen patients received cisplatin-based combination chemotherapy, that were 8 with inadequate stage tumors, 7 with stage III tumors and 1 with stage IV tumor. Follow-up range from 0.02 to 10.48 years, with a median of 3.5 years. Fifty nine patient were alive. Three patients died, all of disease. Recurrence were found in 4 patients. The overall 2-years survival rate was 96% and 10-years survival rate was 94%. In log rank test, residual disease and histology type were significant predictor of survival. (Med J Indones 2002; 11:222-9)Keywords: borderline tumors of ovary, survival